Insights into the passivation effect of atomic layer deposited hafnium oxide for efficiency and stability enhancement in organic solar cells. Issue 30 (18th July 2018) - Polydorou, Ermioni; Botzakaki, Martha; Drivas, Charalampos; Seintis, Kostas; Sakellis, Ilias; Soultati, Anastasia; Kaltzoglou, Andreas; Speliotis, Thanassis; Fakis, Mihalis; Palilis, Leonidas C.; Kennou, Stella; Fakharuddin, Azhar; et al.
Abstract : Atomic layer deposition of HfO2 significantly increases the efficiency and prolongs the lifetime of organic solar cells. Abstract : Atomic layer deposited hafnium oxide is inserted between the zinc oxide electron transport material and the photoactive blend to serve as an ultra-thin passivation interlayer in organic solar cells with an inverted architecture. The deposition of hafnium oxide significantly improves the surface properties of zinc oxide via effective surface passivation and beneficial modification of surface energy; the latter leads to improved nanomorphology of the photoactive blend. As a result, lower recombination losses and improved electron transport/collection at the cathode interface are achieved. A simultaneous increase in open-circuit voltage, short-circuit current density and fill factor is obtained leading to a power conversion efficiency of 6.30% in the ALD-modified cell using a poly(3-hexylthiophene):indene-C60-bisadduct blend as the photoactive layer; this represents a 25% improvement compared to 5.04% of the reference device. Moreover, the incorporation of the passivation interlayer yields a significant stability enhancement in the fabricated solar cells which retain more than 80% of their initial efficiency ( T 80 lifetime) after 750 hours while the reference cell exhibits a T 80 equal to 250 hours.